1984
DOI: 10.1021/jo00190a033
|View full text |Cite
|
Sign up to set email alerts
|

Conformational analysis of sulfur-carbon-phosphorus anomeric interactions. 2. X-ray crystallographic evidence against the importance of nS .fwdarw. .sigma.C-P conjugation in axial 2-[1,3]dithianyldiphenylphosphine oxide

Abstract: The discovery of a predominant axial conformation in 2-[l,3]dithianyldiphenylphosphine oxide (1) was reported recently.1 This finding was remarkable from several points of view: (1) it constituted the first account of the existence of an anomeric interaction between second-row elements sulfur and phosphorus,2 (2) unlike other reported examples

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 0 publications
1
10
1
Order By: Relevance
“…fit is 0.226 A˚ for 9 heavy atoms (S21, S22, S23, P2, C21, C24 C241, C244 and C247), with a maximum deviation of 0.579 A˚ for the S23 atom. These two independent molecules are connected through C-H• interactions (Table S2) shows that the P=O distance in compound 6 (1.486(1) Å falls within the previously observed range (1.481 to 1.492 Å), 1,10,24,25,26,27,28 whereas the P=S distances in two independent molecules of compound 8 (1.962(2) and 1.958(2)) are slightly longer than the previously observed ones (1.946 to 1.952 Å) 10,23 and the P=Se distance in compound 9 (2.1172(8) Å) is also slightly longer that the previously observed ones (2.098 and 2.103 Å). 10,23,27,28,29,30 Crystallographic data (excluding structure factors) have been deposited with the Cambridge Crystallographic Data Centre as supplementary publication no.…”
Section: X-ray Structural Analysessupporting
confidence: 81%
See 1 more Smart Citation
“…fit is 0.226 A˚ for 9 heavy atoms (S21, S22, S23, P2, C21, C24 C241, C244 and C247), with a maximum deviation of 0.579 A˚ for the S23 atom. These two independent molecules are connected through C-H• interactions (Table S2) shows that the P=O distance in compound 6 (1.486(1) Å falls within the previously observed range (1.481 to 1.492 Å), 1,10,24,25,26,27,28 whereas the P=S distances in two independent molecules of compound 8 (1.962(2) and 1.958(2)) are slightly longer than the previously observed ones (1.946 to 1.952 Å) 10,23 and the P=Se distance in compound 9 (2.1172(8) Å) is also slightly longer that the previously observed ones (2.098 and 2.103 Å). 10,23,27,28,29,30 Crystallographic data (excluding structure factors) have been deposited with the Cambridge Crystallographic Data Centre as supplementary publication no.…”
Section: X-ray Structural Analysessupporting
confidence: 81%
“…A search in the Cambridge Structural Database using the C 2 P­(X)­(CS 2 ) fragment reveals only 19 hits, with only 3 referring to carbodithioate derivatives , and the remaining corresponding to di- or trithiate rings. However, a comparison of the PX distances for the whole reference set shows that the PO distance in compound 6 (1.486(1) Å) falls within the previously observed range (1.481–1.492 Å), ,, whereas the PS distances in two independent molecules of compound 8 (1.962(2) and 1.958(2)) are slightly longer than the previously observed ones (1.946–1.952 Å) , and the PSe distance in compound 9 (2.1172(8) Å) is also slightly longer than the previously observed ones (2.098 and 2.103 Å). ,, …”
Section: Resultsmentioning
confidence: 99%
“…Selected bond lengths for 1 and 4 are given in Table 2. The observation [24] that the C-P distance in 4 (equatorial) appears to be significantly longer than that in 1 (axial), as well as the lack of any significant difference in the mean S( l)-C(2) lengths, is contrary to expectations if an ns+ a&. interaction makes an important contribution to the preferred axial conformation in 1.…”
Section: -Axial 12-equatorialcontrasting
confidence: 60%
“…It should be pointed out that such an effect would be a particular example of the repulsive gauche effect [29, 301. In this respect, the experimental evidence [29, 301 indicates that such a gauche effect is expected to be repulsive in S/O and particularly S / S segments. It is therefore surprising that equatorial 4 [24] as well as equatorial 2-(diphenylthiophosphinoyl)-l,3,5-trithiane [3 13 adopt a gauche orientation among heteroatoms (I) rather than one in which the presumed repulsion could be avoided, at least in part (11).…”
Section: -Axial 12-equatorialmentioning
confidence: 99%
“…8 Among various subsequent studies aiming to explain the nature of the "anomeric effect in the S-C-P molecular segment", 9,10 in 1986 it was found that the axial preference of the diphenylphosphinoyl group in 1 (Scheme 1) vanishes in trifluoroacetic acid as solvent. This finding could be in line with neutralization of the electrostatic, attractive interaction between the phosphoryl oxygen and the axial hydrogens H(4,6ax) in 1-ax upon protonation of the phosphoryl oxygen.…”
mentioning
confidence: 99%